Neural correlates of cue reactivity in individuals with smartphone addiction - Schmitgen, Mike; Horvath, Juliane; Mundinger, Christina; Wolf, Nadine D.; Sambataro, Fabio; Hirjak, Dusan; Kubera, Katharina Maria; Koenig, Julian; Wolf, Robert Christian (Addictive behaviors, 2020)
Popularity of smartphones has dramatically increased in the past years, accompanied by increased concerns regarding potentially adverse effects on physical and mental health. Addictive behavior associated with excessive smartphone use, frequently referred to as “smartphone addiction” (SPA), has attracted increased scientific interest. However the neural correlates of SPA are unknown. We used functional magnetic resonance imaging at 3T to investigate the neural correlates of cue reactivity (CR) in individuals with SPA (n = 21) compared to controls (n = 21). SPA was assessed using the Smartphone Addiction Inventory (SPAI), and neural activity was measured by a modified CR task. Contrasts of images of smartphones vs. neutral stimuli and stimuli including active vs. inactive smartphones (p < 0.001, uncorrected for height, followed by correction for spatial extent) were analyzed. In the first contrast, group differences in medial prefrontal (MPFC), occipital, temporal, and anterior cingulate (ACC) cortices, in temporoparietal regions, and cerebellum were found. For active vs. inactive smartphones, group differences were found in frontal operculum/anterior insula and precentral gyrus. Negative correlations were found between MPFC, ACC, precuneus, and precentral gyrus and specific SPAI subscores, i.e. compulsive behavior, functional impairment and withdrawal. This study suggests spatial similarities of CR-related brain activation between addictive smartphone use and other well-known addictive disorders.